2015
DOI: 10.1080/00222348.2015.1125050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metallic Salts of Phenylmalonic Acid on the Crystallization of Poly(L-lactide)

Abstract: The effect of the metallic salts of phenylmalonic acid (PMA), as novel nucleating agents, on the melt and crystallization behaviors, spherulitic morphologies and crystal structures of poly(L-lactide) (PLLA) were studied by means of differential scanning calorimetry (DSC), polarized light microscopy (PLM) and wide angle X-ray diffraction (WAXD). The results showed that calcium and cadmium salts of PMA are good nucleating agents for PLLA. Lithium, sodium, magnesium, strontium and zinc salts of PMA are moderate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…2002D PLLA (the D content 4.25 %, the Mw 1.9 × 10 5 ) was obtained from Nature Works LLC, USA. The magnesium phenylmalonate was synthesized in our laboratory according to the literature [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2002D PLLA (the D content 4.25 %, the Mw 1.9 × 10 5 ) was obtained from Nature Works LLC, USA. The magnesium phenylmalonate was synthesized in our laboratory according to the literature [19].…”
Section: Methodsmentioning
confidence: 99%
“…Salts of phenylmalonic acid, as one of the most important organic metallic salts, exhibit the excellent compatibility with polymer because of its organic section, and the stable structure stemming from its inorganic section, and these advantages have contributed to the use of salts of phenylmalonic acid as efficient functional additives in polymer resin. Thus, salts of phenylmalonic acid including lithium phenylmalonate, calcium phenylmalonate, strontium phenylmalonate, barium phenylmalonate, cadmium phenylmalonate, zinc phenylmalonate, etc., were added to PLLA matrix to investigate their influences on crystallization performances of PLLA [19], it was found that, apart from potassium phenylmalonate, other salts of phenylmalonic acid could serve as nucleating agents for the crystallization of PLLA. However, their work only focused on the comparative study of different salts of phenylmalonic acid for the crystallization of PLLA, the effects of a certain salt of phenylmalonic acid on thermal performances, processing fluidity, and mechanical properties of PLLA were not reported, these studies is very necessary to further reveal the role of MgPA in PLLA matrix.…”
Section: Introduction mentioning
confidence: 99%
“…Upon to now, many compounds with inorganic structures, organic structures, or inorganic/organic hybrid structures had been employed to investigate their nucleation effect on the crystallization process of PLLA. And the current typical nucleating agents include talc [12,13], montmorillonite [14,15], silicon dioxide [16], calcium carbonate [17,18], phenylphosphonate metals [19,20], metallic phenylmalonate salts [21], 1H-benzotriazole derivatives [22,23], benzoyl hydrazine derivatives [24,25], etc. For examples, upon the addition of 0.5 wt % commercial graphene oxide nanoplatelets, the half-time of crystallization of the PLA stereocomplex lower to around 5.5 min at 165°C [26].…”
Section: Wpływ Dihydrazydu Kwasu Bis(3-fenylopropiono) Nn'-dodekanodiowego Jako Promotora Krystalizacji Na Właściwości Termiczne I Optyczmentioning
confidence: 99%
“…And then with the continuous in-depth research, the other commercial or nano-sized inorganic compounds, including hydroxyapatite (17), silica (18), multiwall carbon nanotubes (19), carbon black (20), etc., were used to serve as nucleating agents for crystallization of PLLA. Up to now, some novel synthetic inorganic compounds like nanoscaled zinc citrate complex (21), layered metal phosphonate (22,23), metallic salts of phenylmalonic acid (24,25), and WS 2 nanotube (26) were further developed to be applied in improving the crystallization of PLLA. However, for all inorganic nucleating agents, poor compatibility and dispersity are their inhere defects in PLLA matrix, potentially resulting in phase separation and a decrease of nucleation ability.…”
Section: Introductionmentioning
confidence: 99%